2017
DOI: 10.1038/ismej.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in rhizosphere fungal community during secondary succession following abandonment from agriculture

Abstract: 21Activities of rhizosphere microbes are key to the functioning of terrestrial ecosystems. It is commonly 22 believed that bacteria are the major consumers of root exudates and that the role of fungi is thought to 23 be limited to that of mycorrhizae and pathogens. In order to test the hypothesis that the role of 24 saprotrophic fungi in rhizosphere processes increases with increased time after abandonment from 25 agriculture, we determined the composition of fungi that are active in the rhizosphere along a 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 39 publications
8
137
0
1
Order By: Relevance
“…Bacteria and fungi, two major microbial communities, are vastly different in regard to their morphological traits, growth rates, environmental sensitivities and substrate utilizations (Hannula et al ., ). Numerous studies on soil ecosystems have demonstrated that both bacterial and fungal communities have responded to ecological mechanisms that drive compositional variations (Chen et al ., ; Fan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and fungi, two major microbial communities, are vastly different in regard to their morphological traits, growth rates, environmental sensitivities and substrate utilizations (Hannula et al ., ). Numerous studies on soil ecosystems have demonstrated that both bacterial and fungal communities have responded to ecological mechanisms that drive compositional variations (Chen et al ., ; Fan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced growth (Klironomos 2002) OTUs remain unidentified at the species level (Buée et al 2014;Hannula et al 2017;Mommer et al 2018;Wehner et al 2014). This suggests that there is a large gap between our ability to detect these fungi and our knowledge regarding their identity, let alone their biological functions.…”
Section: Agalinis Gattingeri Aletris Farinosa Gentiana Alba Liatris Smentioning
confidence: 99%
“…In the last decade, next-generation sequencing (NGS) techniques have allowed us to improve our knowledge of soil and root-associated fungal biodiversity in natural ecosystems (Hannula et al 2017;Jumpponen et al 2010;Mommer et al 2018;Wehner et al 2014). Such sequencing techniques provide information about the community composition of fungal operational taxonomic units (OTU) in plant roots, rhizosphere or bulk soil.…”
Section: Soil-borne Pathogenic Fungi In Species-rich Grasslandsmentioning
confidence: 99%
See 2 more Smart Citations